Risk Factors for Type 2 Diabetes Mellitus Relapse in More Than 5-Year Follow-up After Sleeve Gastrectomy with Transit Bipartition - Kirkil, Cueneyt; Yur, Mesut; Aydin, Ilayda; Bozdag, Ahmet; Aslan, Ahmet; Ebiloglu, Mehmet Fatih (Springer, 2025)
Background In some patients who achieved complete remission (CR) of type 2 diabetes mellitus (T2DM) after sleeve gastrectomy with transit bipartition (TB), T2DM relapses after a while. ABCD scoring predicts the likelihood of remission following TB. However, the factors affecting T2DM relapse are unknown. Methods The data of patients with CR after TB who were followed for more than 5 years was analyzed retrospectively. Results The median follow-up of 56 patients, 29 of whom were female (51.8%), was 71 months (range: 61 to 101). Eleven of 56 patients (19.6%) had relapse in T2DM. Patients with an ABCD score less than 4 had a significantly higher rate of relapse. Its sensitivity and specificity rates were 90.9% and 93.3%, respectively. Preoperative C-peptide level (OR 0.032 [CI 0.003-0.295], p = 0.002), LDL-cholesterol level (OR 1.025 [CI 1.005-1.045], p = 0.013), duration of T2DM (OR 1.553 [1.216-1.983], p < 0.001), ABCD score (OR 0.047 [0.006-0.361], p = 0.003), and FIB-4 index (OR 6.073 [1.496-24.656], p = 0.012) were risk factors. Conclusions Patients with longer durations of T2DM, higher LDL-cholesterol levels, lower C-peptide levels and ABCD scores, and worse liver fibrosis are at a higher risk of relapse after achieving initial CR of T2DM with TB.
Keywords: Type 2 diabetes mellitus; Relapse; ABCD score; Transit bipartition